A’s Scarves / Alia Nadirah Mohd Ali - Mohd Ali, Alia Nadirah (2021)
This social media portfolio is one of the assignments in PRINCIPLES OF ENTREPRENEURSHIP (ENT530). For this assignment, I am required to create a business and promoting the business through social media platform, which I have chosen a Facebook Page as the platform for my business. As requested, I chose the business that can give impact towards the Muslim woman lifestyle, which is hijab business. The name of my business is A’s Scarves. A’s Scarves is a clothing and accessories business that selling bawal scarves for Muslim woman. There are 3 sizes available for the bawal which are B45, B50 and B60. Various colour are offered for each of the Bawal Scarves.